Transcriptional regulation in Aspergillus nidulans during nitrogen sufficiency - Downes, Damien J. (Kansas State University, 2015)
Fungi can be found living in a range of environments, including soil and the ocean, and as pathogens of plants and animals. The ability of fungi to adapt to diverse and changing environments is dependent on their ability to sense and respond to an array of signals, including the presence or absence of nitrogen nutrients. Fungi can utilize a diverse array of nitrogen nutrients and do so in a regulated and preferential manner. When preferred nitrogen nutrients such as ammonium and glutamine are present (nitrogen sufficiency), genes required for the utilization of alternative nitrogen sources are not expressed. In the absence of a preferred nitrogen source (nitrogen limitation) the genes for utilization of alternative nitrogen sources are transcriptionally derepressed and can be induced by the presence of a particular nitrogen nutrient, such as nitrate or proline. In the absence of any nitrogen nutrient (nitrogen starvation) the expression of some genes is further elevated. In filamentous fungi the expression of genes required for the utilization of nitrogen nutrients is coordinated by the orthologs of the conserved Aspergillus nidulans GATA transcription factor AreA, which activates transcription of nitrogen utilization genes. AreA activity is controlled by autogenous transcriptional activation, mRNA transcript stability, regulated nucleo-cytoplasmic distribution, and interactions with NmrA, AreB and TamA. The combined effect of these regulatory mechanisms generally results in AreA being inactive during nitrogen sufficiency and active during nitrogen limitation and nitrogen starvation. However, during nitrogen sufficiency AreA remains active at the promoters of some genes, including gdhA, which encodes the key nitrogen assimilation enzyme NADP-dependent glutamate dehydrogenase. In this work we have used both classical genetics and next generation sequencing approaches to examine regulated gene expression and how AreA activity is modulated, primarily during nitrogen sufficiency. We have studied regulation of gdhA to characterize how AreA evades nitrogen metabolite repression. We identify leucine biosynthesis as being a key regulatory signal involved in gdhA expression and characterize the genes required for leucine biosynthesis. We also show that TamA regulates the gdhA promoter by direct DNA binding, which requires interaction with AreA. We have also characterized repression of AreA to identify a potential mode of NmrA corepressor action. Finally, we have characterized the AreA nuclear export signal and explored mechanisms that control regulated nuclear export of AreA.
Keywords: Transcriptional regulation; Aspergillus nidulans; Nitrogen metabolism; Leucine biosynthesis; Fungal genetics; Nuclear export; Genetics (0369); Microbiology (0410); Molecular Biology (0307)